2021
DOI: 10.1186/s10020-021-00332-0
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates lung ischemia/reperfusion injury though the involvement of the MALAT1/microRNA-144/GSK3β axis

Abstract: Background Propofol, an intravenous anesthetic, was proven to protect against lung ischemia/reperfusion (I/R) injury. However, the detailed mechanism of Propofol in lung I/R injury is still elusive. This study was designed to explore the therapeutic effects of Propofol, both in vivo and in vitro, on lung I/R injury and the underlying mechanisms related to metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/microRNA-144 (miR-144)/glycogen synthase kinase-3β (GSK3β). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Currently, no clinical therapies are specifically designed to prevent I/R injury [ 3 ]. PMVEC injury may lead to lung endothelial barrier impairment [ 28 ], and the destruction of PMVECs may affect the normal respiratory function of the lung, thereby reducing the cellular oxygen partial pressure of the lung tissue and inducing hypoxia response [ 29 ]. Therefore, the present study constructed an in vitro cell model of H/R using PMVECs, in combination with in vivo H/R rat models, aiming to explore the effects of miR-141-3p, SIRT1 and Beclin-1 in collaboration on H/R injury of PMVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no clinical therapies are specifically designed to prevent I/R injury [ 3 ]. PMVEC injury may lead to lung endothelial barrier impairment [ 28 ], and the destruction of PMVECs may affect the normal respiratory function of the lung, thereby reducing the cellular oxygen partial pressure of the lung tissue and inducing hypoxia response [ 29 ]. Therefore, the present study constructed an in vitro cell model of H/R using PMVECs, in combination with in vivo H/R rat models, aiming to explore the effects of miR-141-3p, SIRT1 and Beclin-1 in collaboration on H/R injury of PMVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol, an intravenous anaesthetic, was shown to impedes autophagy activation and secretion of inflammatory factors (e.g., TNF-α, IL-18, and IL-1β) through reducing the MALAT1-miR-144-GSK3β signaling axis. Propofol eventually alleviated lung ischemia-reperfusion in mice (Zhang et al, 2021). Although these findings imply that the use of these drugs targeting MALAT1 could be effective in treating various lung diseases, further research is necessary to fully understand their precise mechanisms of action.…”
Section: Malat1 As a Therapeutic Target In Lung Diseasementioning
confidence: 93%
“…An experimental study carried out on laboratory animals by Zhang et al, investigating the expression of certain biological markers, such as microRNAs-144, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), and glycogen synthase kinase-3β (GSK3β) in LIRI, showed that the overexpression of genes was directly proportional to the intensity of the ischemic injury. Regarding the epigenetic expression of microRNA-144, the authors reported a decrease in its concentration [ 165 ]. Li et al studied the expression of microRNA-146a in LIRI and showed a decrease in the epigenetic expression in pulmonary ischemic injury.…”
Section: Implications Of Genetic and Epigenetic Expression On Inflamm...mentioning
confidence: 99%